Adherence to a Healthy Nordic Diet and Risk of Stroke: A Danish Cohort Study. Issue 2 (February 2017) - Hansen, Camilla Plambeck; Overvad, Kim; Kyrø, Cecilie; Olsen, Anja; Tjønneland, Anne; Johnsen, Søren Paaske; Jakobsen, Marianne Uhre; Dahm, Christina Catherine
Abstract : Background and Purpose—: Specific dietary patterns, including the Mediterranean diet, have been associated with stroke prevention. Our aim was to investigate whether adherence to a healthy Nordic diet, including fish, apples and pears, cabbages, root vegetables, rye bread, and oatmeal, was associated with risk of stroke. Methods—: Incident cases of stroke among 55 338 men and women from the Danish Diet, Cancer and Health cohort were identified from the Danish National Patient Register and verified by review of records. Cases of ischemic stroke were further subclassified based on etiology according to the TOAST classification system (Trial of Org 10172 in Acute Stroke Treatment). Information on diet was collected at baseline (1993–1997) using a semiquantitative food-frequency questionnaire. Cox proportional hazards models were used to estimate hazards ratios of total stroke and subtypes of ischemic and hemorrhagic stroke. Results—: During a median follow-up of 13.5 years, 2283 cases of incident stroke were verified, including 1879 ischemic strokes. Adherence to a healthy Nordic diet, as reflected by a higher Healthy Nordic Food Index score, was associated with a lower risk of stroke. The hazards ratio comparing an index score of 4 to 6 (high adherence) with an index score of 0 to 1 (low adherence) was 0.86 (95% confidence interval 0.76–0.98) for total stroke. Inverse associations were observed for ischemic stroke, including large-artery atherosclerosis. No trend was observed for hemorrhagic stroke; however, a statistically insignificant trend was observed for intracerebral hemorrhage. Conclusions—: Our findings suggest that a healthy Nordic diet may be recommended for the prevention of stroke. Abstract : Supplemental Digital Content is available in the text.